EVALUASI UJI EFEKTIVITAS EKSTRAK KAYU MANIS (Cinnamomum burmanni) SEBAGAI LARVASIDA TERHADAP KEMATIAN JENTIK NYAMUK (Aedes aegypti) - Ike Widiya R (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2023)
Alternative larvicides against Aedes aegypti larvae and safe for the environment, one of which is cinnamon oil which has been shown to have a larvicidal effect on larvae. Cinnamon contains flavonoid compounds which are strongly suspected to have a larvicidal effect. It can be said that this research is to determine the effectiveness of extracts from cinnamon as a larvicide against the death of Aedes aegypti mosquito larvae. And for the extraction method used in this study using the maceration method. For a concentration of 2% it can kill a total of 32 (53%) larvae, and for a concentration of 4% it can kill 43 (72%) total lava, and a concentration of 6% can kill 53 (88%) larvae, and for a positive control, namely abate (temephos). ) has the best larvicidal effect with an average % larval mortality of 100% within 1 hour. Cinnamon extract test treatments with a concentration of 2% (2ml/100ml) experienced larval death 32 (43%), and for a concentration of 4% (4ml/100ml) experienced larvae mortality 43 (53%). and for a concentration of 6%, 53 (88%) larvae died. And for temephos, it was able to kill a total of all larvae, while for negative control it did not die. The most effective concentration of cinnamon extract in killing larvae was 6%, the higher the concentration, the higher the larval mortality value.